Mapping knowledge structure and research of the biologic treatment of asthma: A bibliometric study - Sun, Jiamin; Bai, Shiyao; Zhao, Jieyu; Li, Danling; Ma, Xueqing; Ma, Lin; Su, Xinming (Frontiers in Immunology, 2023)
Background: Bronchial asthma is a chronic inflammatory disease of the airways involving a variety of cells and cellular components that manifests clinically as recurrent episodes of wheezing, shortness of breath, with or without chest tightness or cough, along with airway hyperresponsiveness and variable airflow limitation. The number of people with asthma has reached 358 million worldwide and asthma causes huge economic loss. Methods: Publications related to biologics in asthma published from 2000-01-01 to 2021-12-31 were retrieved from Web of Science Core Collection. The search strategies were as follows: topic: TS=("biological products " OR "biologics") AND TS=asthma. The document type was set to articles and review with language restriction to English. Three different analysis tools including one online platform, VOS viewer1.6.18, and CiteSpace V 6.1.R1 software were used to conduct this scientometric study. Results: The sample in this study was comprised of a total of 598 publications by 2,396 authors affiliated with 1054 organizations in 64 countries. We have summarized the top 10 authors, countries or regions, institutions, and journals by publication volume. America makes significant contributions in this area and was the most productive country in the world. The Journal of Allergy and Clinical Immunology in Practicet publishes the most literature in this area, with immunology, The Journal of Allergy and Clinical Immunology in Practice is the journal that publishes the most literature in this field. Immunology, allergic reactions, and respiratory system are the three most relevant subject categories. Bachert, claus is the scholar with the most publications, and univ colorado is the institution with the most publications. By analyzing the keywords, we can obtain three clusters, 19 burst words and two research trends, and it is hoped that more relevant biological agents can be developed and applied in the treatment of asthma to achieve individualized treatment and management of asthma.Conclusion: This study demonstrates the global research hotspots, trends and clinical use of biologic Treatment of asthma. It can help scholars to quickly understand the current status and hotspots of research in this field, and also provide some guidance and reference for those who are currently researching in this area.